Responses and opinions on the forms of exaggeration and hyperbole in Arabic - Ameen , Dr.Ali Sami (Thi Qar Arts Journal, 2024)
This is an old new topic, an old topic, because the scholars of the linguistic lesson turned to it from an early date. Many arab scholars and its ancientand modren scientists and researchers were interested in  studaying this subject. It is new considering the findings of these scientists and researchers, and their opinion, that could be the subject of new research, and the emergence of innovative ideas, and then  I proceeded to write these pages to discuss a set of issues concerning the formulas of exaggeration in arabic language, and some of whate was said about it. I found some of these are inaccurate, and ther is a lot of arguments, and evidence to weaken, reject it , and correct the matter as much as possible, using the lexical connotation of formulas and materials, and sometimes making other statistics. while the study of the other section leads to the conclusion of set of opinions which in one way or another contributes to an understanding of how the exaggeration of formulas emerge, and  related to this a ways of deriving these Formulas and evolution, as well as trying to solve some of the problems that relate to this formula or that. the research was divide on several topics, some of them devoted to the verb formulas that were said to indicate an exaggeration, and the other dealt with the issues related to the structures of exaggeration in the qualities,its connotation, its prevalence and its derivation .